2012
DOI: 10.5194/bgd-9-10285-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CO<sub>2</sub> increases <sup>14</sup>C-primary production in an Arctic plankton community

Abstract: Responses to ocean acidification in plankton communities were studied during a CO2-enrichment experiment in the Arctic Ocean, accomplished from June to July 2010 in Kongsfjorden, Svalbard (78°56, 2' N, 11°53, 6' E). Enclosed in 9 mesocosms (volume: 43.9–47.6 m3), plankton was exposed to CO2 concentrations, ranging from glacial to projected mid-next-century levels. Fertilization with inorganic nutrients at day 13 of the experiment supported the accumulation of phytoplankton biom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 83 publications
8
58
4
Order By: Relevance
“…This imbalance generally occurs when nutrients are depleted and often results in increased DOC leakage from the cells. Carbon overconsumption may also occur as a response to increased pCO 2 [7,53]. Since nutrient levels were kept replete in this study, the increased DOC excretion is most likely a direct effect of elevated DIC levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This imbalance generally occurs when nutrients are depleted and often results in increased DOC leakage from the cells. Carbon overconsumption may also occur as a response to increased pCO 2 [7,53]. Since nutrient levels were kept replete in this study, the increased DOC excretion is most likely a direct effect of elevated DIC levels.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Engel et al [53] reported on average 21-23% PP DOC of PP TOT in mesocosms with a natural Arctic phytoplankton community exposed to different pCO 2 treatments. Generally, DOC release in natural marine phytoplankton communities does not exceed 40% of the total primary production [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analysis of the TEP concentrations from the same experiment by Egge et al (2009) showed no difference in TEP production between the different pCO 2 treatments. Recently, experiments using mesocosms in Arctic waters showed enhanced production of DOC by phytoplankton grown under elevated CO 2 (Engel et al, 2013).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Experimental research from the European Arctic suggests that increasing CO 2 concentrations enhance primary production in nutrient-replete conditions 16 , although this response is possibly species-specific owing to varying efficiencies of the mechanisms for concentrating cellular carbon 17 . However, the response to increased CO 2 when combined with warming may deviate from the expected additive effect.…”
mentioning
confidence: 99%